Numerical analysis on dynamic response characteristics of geosynthetic reinforced embankment under moving load - ZHANG Ling; OU Qiang; ZHAO Ming-hua; DING Xuan-ming; LIU Jian-fei (Rock and Soil Mechanics, 2021)
The dynamic response of geosynthetic reinforced embankment under traffic moving load has attracted increasing attentions in the engineering field. A 3D model of geosynthetic reinforced embankment was established by using the ABAQUS finite element software in this paper, which was used to analyze the dynamic stress and deformation of geosynthetic reinforced embankment under moving load. The traffic load was simulated by two moving rectangular plane loads. Fortran subroutine was developed to control the amplitude, range, and speed of the moving load. The equivalent linear viscoelastic model was developed to simulate embankment fill to reflect the viscoelasticity of embankment fill. The geogrid was simulated by T3D2 truss element. The infinite element was used to reduce the boundary effect caused by model size. The numerical model of geosynthetic reinforced embankment under moving load was established without considering drainage consolidation. Based on the results of the existing literature and the results of this paper, the cross-section deformations of the geosynthetic reinforced embankment and the stress at the embankment top surface were compared and verified. The dynamic stress distribution in the longitudinal section and transverse section and the vertical dynamic stress distribution characteristics of the geosynthetic reinforced embankment under moving load were also analyzed. The results showed that the dynamic stress and deformation decayed rapidly within the range of 1.0 m on the embankment top surface and gradually transitioned to an equivalent uniform load with small amplitude. At the same depth, the attenuation coefficient of dynamic stress under the wheel load was the smallest, followed by that at the center of double wheel loads, and the attenuation coefficient at the outer edge of the wheel load was the largest.